Exploring the qualities of midwifery-led continuity of care in Australia (MiLCCA) using the quality maternal and newborn care framework. Issue 2 (March 2020) - Cummins, Allison; Coddington, Rebecca; Fox, Deborah; Symon, Andrew
Abstract: Problem: Midwifery-led continuity of care has well documented evidence of benefits for mothers and babies, however uptake of these models by Australian maternity services has been slow. Background: It is estimated that only 10% of women have access to midwifery-led continuity of care in Australia. The Quality Maternal Newborn Care (QMNC) Framework has been developed as a way to implement and upscale health systems that meet the needs of childbearing women and their infants. The Framework can be used to explore the qualities of existing maternity services. Aim: We aimed to use the QMNC Framework to explore the qualities of midwifery-led continuity of care in two distinct settings in Australia with recommendations for replication of the model in similar settings. Methods: Data were collected from services users and service providers via focus groups. Thematic analysis was used to develop initial findings that were then mapped back to the QMNC Framework. Findings: Good quality care was facilitated by Fostering connection, Providing flexibility for women and midwives and Having a sense of choice and control . Barriers to the provision of quality care were: Contested care and Needing more preparation for unexpected outcomes . Discussion: Midwifery-led continuity of carer models shift the power dynamic from a hierarchical one, to one of equality between women and midwives facilitating informed decision making. There are ongoing issues with collaboration between general practice, obstetrics and midwifery. Organisations have a responsibility to address the challenges of contested care and to prepare women for all possible outcomes to ensure women experience the best quality care as described in the framework. Conclusion: The QMNC Framework is a useful tool for exploring the facilitators and barriers to the widespread provision of midwifery-led continuity of care.